1981
DOI: 10.1111/j.1469-8749.1981.tb02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinaesthetic Sensitivity to Passive Movements and its Relationship to Motor Development and Motor Control

Abstract: SUMMARY A test of kinaesthetic sensitivity to passive movements of the upper limbs was constructed consisting of two tasks: position and movement discrimination, and movement pattern perception and memory. 475 subjects ranging in age from five years to adult were tested and developmental trends were established. The test was found to be a useful tool in measuring the kinaesthetic sensitivity of normal subjects, as well as of intellectually and physically handicapped children. Results for right and left arms di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(51 citation statements)
references
References 2 publications
3
47
1
Order By: Relevance
“…Previous research has established that kinesthetic sensitivity and acuity improves in middle childhood and continues to approach adult levels during late adolescence (Laszlo and Bairstow, 1980; Bairstow and Laszlo, 1981; Elliott et al, 1988; Visser and Geuze, 2000; Goble et al, 2005; Pickett and Konczak, 2009). However, no consistent assessment protocol has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has established that kinesthetic sensitivity and acuity improves in middle childhood and continues to approach adult levels during late adolescence (Laszlo and Bairstow, 1980; Bairstow and Laszlo, 1981; Elliott et al, 1988; Visser and Geuze, 2000; Goble et al, 2005; Pickett and Konczak, 2009). However, no consistent assessment protocol has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have questioned the value of research into acuity for passive movements as being ecologically less valid (Elliot et al 1988). On the other hand, using a procedure which does not require active movements has some definite advantages, particularly in testing patients with severe motor disorders (Bairstow and Laszlo 1981). Furthermore, although the nature of the relation between 'passive' kinaesthetic acuity and general motor skills may be unclear (Sims and Morton 1998), the existence of such a relation can hardly be denied.…”
mentioning
confidence: 99%
“…Laszlo 1981, Laszlo andBairstow 1983). Using their Kinaesthetic Sensitivity Test (KST), Laszlo and Bairstow (1985) required subjects to sense the position of their arms, which were moved by the experimenter.…”
mentioning
confidence: 99%
“…if one hand is above and one below a table, this tests the egocentric mapping of proprioceptive cues, rather than proprioceptive sensitivity per se). Laszlo and Bairstow have strongly argued that kinaesthetic dysfunction is a major component of the problem in DCD (Bairstow and Laszlo 1981;Laszlo and Bairstow 1983, 1985. On the basis of this work, they have suggested that kinaesthetic training should be employed as a therapy.…”
mentioning
confidence: 99%